Some structural properties of recombinant HIV-1 protease - Hong Loan, Nguyen Thi; Sang, Nguyen Van; Thai, Trinh Hong; Nghia, Phan Tuan; Thuan, Bui Phuong (Academia Journal of Biology, 2016)
HIV-1PrHis Protease was produced in the recombinant form of 114 amino acid residues (ca. 12.8 kDa), consisting of 99 amino acid peptide of HIV-1 protease fused with TEV and 6xHis sequences at the C terminal. The MS/MS analysis indicated that the amino acid sequence of HIV-1PrHis was exactly the same as theoretically designed. The circular dichroism spectrum of the HIV-1PrHis showed clear β sheet with a negative peak at 205 nm and intensity of nearly -8 mdeg. By using ProMod-II software and based on 3D structures of reported HIV-1 proteases, 3D structure of the HIV-1PrHis was deduced, it had RMSD of 0.154 Å; TM-score of 0.9882 and Z-core in the same range of the known HIV-1proteases analyzed by NMR and X-ray diffraction. The obtained results will enable to use the recombinant HIV-1PrHis for screening its inhibitors.